National Swine Research and Training Center, Suwanwajokkasikit Institute, Kasetsart University, Bangkok 10900,Thailand. - Montatip Yunchalad; Yu Konglin; Ngamjit Lowithun; Winus Puminat; Siriporn Stonsaovapak (Agriculture and Natural Resources, 2002)
A preliminary study for alleviating pollution from mango processing brine was conducted by recycling spent brines. Spent brines were reclaimed by a sand filtration and an acitvated carbon system. The comparative physico-chemical characteristics of influent and effluent spent brines were investigated. It was found that the values of pH and acidity of effluent brine changed significantly while there was no change in NaCl content. The effluent brine became a visual clear corresponding to a settleable solid, and there were no substantial changes in the total solid without an objectionable odor. Mango brining experiment from defrozen, reclaimed brine and fresh brine were conducted. Pickled mango from reclaimed brine was as good as the pickled mango from fresh brine. The quality of reclaimed brine should be studied during extensive storage at room temperature. A comparison of 4 samples of sweet and sour pickled mango were done and evaluated by a preference test. The overall conclusion from the tasting panel on all samples of sweet and sour pickled mango was that there was not a significant difference in color, odor, flavor, texture or acceptability. Furthermore, the capacity of the reclamation system was also estimated. Results showed that a substantial changes in the chemical composition were significantly different for 15 liters of effluent brine, but for 12 liters of effluent brine, there was only some changes in total solid and dissolved solid. Therefore, further experiment should be performed to large - scale operations for potential recycling brine evaluation.